RANCANG BAGUN SISTEM INFORMASI AGENDA KERJA UNTUK ANGGOTA KEPOLISIAN BERBASIS KINERJA MENGGUNAKAN METODE BERORIENTASI OBJEK - Edy Siswanto; Sugiarto Sugiarto (Elkom : Jurnal Elektronika dan Komputer, 2021)
Within the body of the National Police, the Polsekta / Polsek have an important role in protecting, nurturing, serving and enforcing the law in the Tegowanu Police area community. Therefore, the Tegowanu Police are required to be able to serve the community where one of the main tasks of the Republic of Indonesia Police is as a public servant. As one of the law enforcement officers, the National The old work agenda system still uses manual methods and takes a lot of time and with this system will slow down the performance of Polsek members. Documentation of activities carried out by the Tegowanu Police Officer cannot be seen by the police chief and members, because photo documentation is only stored on the officer's computer. Another problem is that there is no data storage for community activity data and activity schedules, because there is no storage in the database so that data processing has not been well integrated. By designing a Performance-based Activity information system using the Object Oriented Method at the Tegowanu Police, Resort Grobogan is expected to help data processing so that it is more well integrated and the reporting process and data retrieval are faster if data is needed at any time and create an integrated system with the database. The information that will be built can speed up the process of processing and sending information and activities of the Tegowanu Police to the head of the Sector Police.